2002
DOI: 10.1074/jbc.m112088200
|View full text |Cite
|
Sign up to set email alerts
|

Familial Amyotrophic Lateral Sclerosis-associated Mutations Decrease the Thermal Stability of Distinctly Metallated Species of Human Copper/Zinc Superoxide Dismutase

Abstract: We report the thermal stability of wild type (WT) and 14 different variants of human copper/zinc superoxide dismutase (SOD1) associated with familial amyotrophic lateral sclerosis (FALS). Multiple endothermic unfolding transitions were observed by differential scanning calorimetry for partially metallated SOD1 enzymes isolated from a baculovirus system. We correlated the metal ion contents of SOD1 variants with the occurrence of distinct melting transitions. Altered thermal stability upon reduction of copper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
233
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(247 citation statements)
references
References 30 publications
13
233
1
Order By: Relevance
“…SDS (second lane of each set). This result suggested increased SDS binding to these mutants, possibly as a consequence of unfolding in this gel system, which was consistent with the established importance of metal binding to SOD1 for both chemical and thermal stability (19,21,22).…”
Section: Both Wt-like and Metal Binding Region Als-related Sod1 Mutansupporting
confidence: 70%
See 3 more Smart Citations
“…SDS (second lane of each set). This result suggested increased SDS binding to these mutants, possibly as a consequence of unfolding in this gel system, which was consistent with the established importance of metal binding to SOD1 for both chemical and thermal stability (19,21,22).…”
Section: Both Wt-like and Metal Binding Region Als-related Sod1 Mutansupporting
confidence: 70%
“…Our data suggest that cellular disulfide reducing influences at physiological temperature and pH are sufficient to convert relatively well folded WT-like SOD1 mutants (18) or less stable metal-binding region mutants (19) into more severely destabilized species. These non-native mutant forms might resemble the subset of highly unstable SOD1 C-terminal truncation mutants (15,64), which also lack the disulfide bond consequent to deletion of Cys-146.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…9). Several papers (41,46) have also reported that H46R is less stable than other FALS mutants in vitro. Most interestingly, the immunoreactivities of H46R against the mAbs in Western blot and ELISA were similar to that of WT or C111S (Figs.…”
Section: Discussionmentioning
confidence: 99%